2022
DOI: 10.3390/nu14245214
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroquercetin Supplementation Improved Hepatic Lipid Dysmetabolism Mediated by Gut Microbiota in High-Fat Diet (HFD)-Fed Mice

Abstract: Dihydroquercetin (DHQ) is a natural flavonoid with multiple bioactivities, including hepatoprotective effects. This study aimed to investigate whether DHQ improved lipid dysmetabolism in the body, especially in the liver, and whether there is a relationship between hepatic metabolism and altered gut flora in high-fat diet (HFD)-induced mice. HFD-induced mice were given 50 mg/kg body weight DHQ intragastrically for 10 weeks. The data showed that DHQ reduced body weight, the weight of the liver and white adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(80 reference statements)
1
1
0
Order By: Relevance
“…This suggest that Lactococcus might have adverse effects on lipid metabolism homeostasis, and Muribaculum beneficial effects on plasma cholesterol. This is consistent with previous studies showing that Muribaculum relative abundance is lower in WD-fed mice ( 89 ) and obese mice fed a HFD ( 90 , 91 ) than in ND mice, and that Lactococcus richness is increased in animals fed a HFD ( 92 , 93 ). Thus, the present results suggest that Muribaculum and Lactococcus are bacteria associated with Totum-070 beneficial effect on lipid disorders caused by WD.…”
Section: Discussionsupporting
confidence: 93%
“…This suggest that Lactococcus might have adverse effects on lipid metabolism homeostasis, and Muribaculum beneficial effects on plasma cholesterol. This is consistent with previous studies showing that Muribaculum relative abundance is lower in WD-fed mice ( 89 ) and obese mice fed a HFD ( 90 , 91 ) than in ND mice, and that Lactococcus richness is increased in animals fed a HFD ( 92 , 93 ). Thus, the present results suggest that Muribaculum and Lactococcus are bacteria associated with Totum-070 beneficial effect on lipid disorders caused by WD.…”
Section: Discussionsupporting
confidence: 93%
“…Excessive production of ROS or insufficient antioxidant function of cells will cause endogenous oxidation, resulting in more synthesis of some or some proteases in the body, resulting in the formation of oxidation products [18]. It has been reported that DHQ can reduce the activity of xanthine oxidase to achieve the purpose of antioxidation [19]. DHQ can inhibit inflammation by reducing the expression of pro-inflammatory mediators and reducing the activity of inflammation-related protein genes and inflammation-related enzymes [20].…”
Section: Introductionmentioning
confidence: 99%